Analysis of The Financial Performance of PT. Adhi Karya (Persero) Tbk Listed on The Indonesia Stock Exchange - Marisya, Fitria (CV. Picmotiv, 2023)
The purpose of this study is to measure the company's financial performance based on the financial statements of a company using analysis of liquidity, solvency, and profitability ratios. The report used is every account in the balance sheet and income statement. The financial statements discussed are the financial statements of PT Adhi Karya (Persero) Tbk for the 2019-2020 period. The results of this study show that PT Adhi Karya (Persero) Tbk for the 2019-2020 period has poor financial performance. This is due to the company's lack of ability to meet short-term obligations and long-term obligations as well as the company's lack of ability to earn profits for 1 (four) period from 2019-2020. With this, the company is expected to be able to increase profits and be able to streamline the costs incurred in the company